New York City [videorecording (DVD)] - Wallace, Tina (WowNow Entertainment, 2022)
Tracing its origins to a trading post founded on the southern tip of Manhattan Island by Dutch colonists in 1624, New York City has been an incubator of some of the greatest architecture, literature, music, and arts. Find out about the amazing American city that never sleeps.